Risk factors for diabetic nephropathy in chronic kidney disease: A narrative review (Research, Society and Development, 2025)
Diabetic Nephropathy (DN) is characterized by a group of vast clinical or subclinical manifestations, which affect the Peripheral Nervous System (PNS) as a complication of Diabetes Mellitus (DM). DN affects 20 to 40% of patients with type 1 Diabetes Mellitus (DM) and at least one in three of those with type 2 DM. This study is a narrative review with the purpose of discussing and describing the main risk factors for DN in CKD in its clinical context. The following databases were used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with language restrictions (Portuguese) and giving priority to articles published between 2010 and 2022. This review highlights the importance of ND in the scenario of morbidity and mortality in patients with DM. In addition to its high prevalence, it is associated with a high frequency of CKD, making it the second most costly diabetic complication. As risk factors are associated with a genetic predisposition, lifestyle habits and chronic diseases, further studies on the molecular bases of the disease, other mediators of kidney damage and therapy are still necessary in order to prevent and delay kidney complications caused by DM.